2015
DOI: 10.4236/pp.2015.611054
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Studies on the Leaf Extract and Active Fractions of <i>Newbouldia laevis</i> (Bignoniaceae)

Abstract: Optimal control of chronic hyperglycemia prevents both micro and macro vascular complications-a leading cause of morbidity and mortality in diabetic subjects. This study was undertaken to give credence to the traditional use of Newbouldia laevis leaves in the treatment of diabetes mellitus (DM). Dichloromethane-methanol (1:1) extract (DME) of N. laevis leaves was prepared by cold maceration. Separation of DME into column chromatographic fractions yielded the n-hexane fraction (HF), ethylacetate fraction (EF) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…In this study, induction of diabetes with alloxan is demonstrated to be associated with a characteristic decrease in body weight. The ability of DME to protect against massive weight loss in alloxan diabetic rats seems to be due to its ability to improve glucose utilization, reduce hepato-renal dysfunction, [18] [79], improve the TAS and restore haematopoetic function. Earlier report noted a significant increase in the body weight of normal rats supplemented with N. laevis extract [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, induction of diabetes with alloxan is demonstrated to be associated with a characteristic decrease in body weight. The ability of DME to protect against massive weight loss in alloxan diabetic rats seems to be due to its ability to improve glucose utilization, reduce hepato-renal dysfunction, [18] [79], improve the TAS and restore haematopoetic function. Earlier report noted a significant increase in the body weight of normal rats supplemented with N. laevis extract [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the antihyperglycemic activity of the leaf extract and active fractions of the plant was reported [18] and apigenin was reported to be one of the active metabolites responsible for the antihyperglycemic activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…to slow the progression of this disorder, diabetes mellitus and its associated complications continue to pose a major health challenge to people (Ravi et al, 2005;Kavishankar et al, 2011). In view of this, alternative approaches are therefore urgently needed to manage it (Osigwe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although, the aqueous leaf extract of N. laevis have been reportedly evaluated by Omonkhelin et al, and Owolabi et al, for its antihyperglycaemic activity at 100, 200 and 400 mg/kg body weight 31,36 as well as Ajah et al, and Osigwe et al, at 200 and 250, 500, 1000 mg/kg body weight 37,38 respectively in alloxan-induced hyperglycaemic rats, there is dearth of information in the open scientific literature on the possibility of antidiabetic activity of N. laevis leaf on alloxan-induced hyperglycaemia especially at the specific pharmacologic dose of 100 and 200 mg/kg body weight. Therefore, the present study was undertaken to provide information on the antihyperglycaemic effects of aqueous leaf extract of N. laevis on alloxan-induced hyperglycaemia in rats.…”
mentioning
confidence: 99%